Assessing immobilization matrices for nuclear effluent treatment: Cs case study - Lopes Costa e Silva, Danilo; Alves Fungaro, Denise; Las Casas, Alexandre; Sergio Cardoso da Silva, Paulo; Vicente, Roberto; Silva de Araujo, Mariana; Carvalho Izidoro, Juliana; Mello-Castanho, Sonia (Journal of Applied Materials and Technology, 2024)
The immobilization processes for nuclear waste have gained significant attention from the scientific community due to the growing global activity in the nuclear industry. Although these processes have been studied and applied since the mid-20th century, many questions remain that require further in-depth research, including the immobilization itself and the deposition of wasteforms in repositories designed to safeguard against future exposure. In this study, highly phase-pure zeolite A was synthesized via hydrothermal processing of coal fly ash from a Brazilian thermal power plant and loaded with Cs to evaluate thermal stability, structure, and immobilization in Nb-aluminoborosilicate and geopolymer matrices. Cs adsorption, confirmed by XRD peak intensity and Raman band changes, showed a 26 wt.% incorporation (INAA) after 24-hour sorption using simulated CsCl solution, a notable result given the fly ash impurities. The zeolite structure remained stable during the heating up to 960 °C, forming water-insoluble phases (pollucite and cesium aluminum oxide) right after structural collapse between 700 °C and 900 °C. Up to 40 wt.% of Cs-loaded waste was incorporated into a monolithic ceramic via thermal treatment of Nb-aluminoborosilicate glass and zeolite A at 900 °C for 2 hours, yielding a dense body (2.4 g/cm³) with low porosity (3.6%) and water absorption (1.63%). In contrast, raw Cs-loaded zeolite A showed high porosity (48%), water absorption (33%), and low density (1.44 g/cm³). Crystalline Cs phases formed at lower temperatures (900 °C) due to the devitrification nature of the glass. Geopolymer matrices immobilizing Cs-loaded zeolite exhibited water leachability comparable to similar materials, meeting nuclear waste disposal requirements.